2020
DOI: 10.5194/tc-14-211-2020
|View full text |Cite
|
Sign up to set email alerts
|

A decade of variability on Jakobshavn Isbræ: ocean temperatures pace speed through influence on mélange rigidity

Abstract: Abstract. The speed of Greenland's fastest glacier, Jakobshavn Isbræ, has varied substantially since its speed-up in the late 1990s. Here we present observations of surface velocity, mélange rigidity, and surface elevation to examine its behaviour over the last decade. Consistent with earlier results, we find a pronounced cycle of summer speed-up and thinning followed by winter slowdown and thickening. There were extended periods of rigid mélange in the winters of 2016–2017 and 2017–2018, concurrent with termi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(115 citation statements)
references
References 59 publications
3
112
0
Order By: Relevance
“…After the arrival of cold water in 2016, Jakobshavn Isbrae slowed, advanced and thickened (Khazendar et al, 2019;Joughin et al, 2020). During the 2019 summer melt season, however, Jakobshavn accelerated and thinned enough that yearly elevation change became negative for the rst time in 4 years.…”
Section: Thinning and Acceleration Of Jakobshavn Isbrae In 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…After the arrival of cold water in 2016, Jakobshavn Isbrae slowed, advanced and thickened (Khazendar et al, 2019;Joughin et al, 2020). During the 2019 summer melt season, however, Jakobshavn accelerated and thinned enough that yearly elevation change became negative for the rst time in 4 years.…”
Section: Thinning and Acceleration Of Jakobshavn Isbrae In 2019mentioning
confidence: 99%
“…These melting rates depend on both fjord temperature and the volume of meltwater discharge that ows along the glacier's bed during summer (Jenkins, 2011). In contrast, Joughin et al (2020) suggested that fjord water temperatures affected the glacier by controlling the stiffness of the ice mélange that lls the fjord. This hypothesis suggests that during the winter, ice mélange stiffens and exerts increased back-stress against the glacier front (Amundson et al, 2010;Cassotto et al, 2015).…”
mentioning
confidence: 99%
“…However, ice mélange can also exist without substantial sea ice coverage if iceberg productivity is sufficiently high, such as at Jakobshavn Isbræ, Helheim Glacier and Kangerdlugssuaq Glacier, Greenland. At these glaciers, ice mélange is held together by iceberg–iceberg and iceberg–bedrock contact forces (Joughin and others, 2008; Amundson and others, 2010; Seale and others, 2011; Jakobsson and others, 2012; Amundson and Burton, 2018), although sea ice growth in winter likely provides additional rigidity (Cassotto and others, 2015; Robel, 2017; Bevan and others, 2019; Joughin and others, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…PANGAEA.897066 (Zhang et al, 2019). The post-2017 calving fronts delineated from TerraSAR-X data are available at the University of Washington Research Works Archive at https://doi.org/10.6069/XQS7-CD47 (Joughin et al, 2020). Landsat-8 imagery are available from EarthExplorer (https://earthexplorer.usgs.gov, last access: June 2020).…”
Section: Discussionmentioning
confidence: 99%